Application of Concept Maps for Conducting Research in Adult Education - Simone C.O. Conceicao; Susan M. Yelich-Biniecki; Anita J. Samuel (Adult Education Research Conference, 2015)
The purpose of this paper is to identify and analyze existing literature in which concept maps specifically were utilized as a research tool. By theorizing from the literature and making connections among different approaches that use concept maps, adult educators-scholars can broaden their understanding of the application of concept maps in adult education research. This paper shows how concept maps can be used as productivity tools for conducting individual and collaborative research and instructional tools for teaching Research Methods courses.
Keywords: concept maps; research methods; application tools